Arguments and Actions in Social Theory - Preston, P. author. aut Link
VII, 189 p.
Keywords: This book argues that theorists are located within the social world; exercises in theorizing are both bounded and creative; imagination and creativity build upon the resources of tradition; and such awareness is the basis for dialogue with the denizens of other traditions, cultures and ways of making sense of the world.